ANALISIS TEKNIK HUMOR PADA CHANNEL YOUTUBE MARYMARYMARY: KAJIAN PRAGMATIK - Putri Dwiyana Maulani (WIDAI Japanese Journal, 2023)
The purposes of this research are to describe verbal humor techniques based on the Berger’s theories (2017), in the humor utterances at the Youtube Channel MaryMaryMary (マリマリマリー). The humor utterances are identified based on the contexts and theory of incongruities to avoid subjectivity of humor data. This research is categorized into descriptive qualitative research using pragmatic approach. The coverage of research object at the channel Youtube MaryMaryMary (マリマリマリー) is reduced based on the characteristics of the chracters as needed in this research. The total data found are 32 data which consist of single and intersectional data. 32 data are distributed in 15 verbal humor techniques from Berger (2017). From the anasysis, it can be concluded that misunderstanding humor techniques and violation of relevance maxim are most frequently appered in humor utterances in the research object.